ANALISIS KESALAHAN EJAAN, DIKSI, DAN KALIMAT EFEKTIF DALAM PENULISAN SURAT DINAS DI KANTOR DESA KIUNG - Julianus Julianus; Hotma Simanjuntak; Sesilia Seli (Universitas Tanjungpura, 2020)
AbstractResearchers are interested in examining official letters because there are still many language errors, especially in the use of spelling, word choices, and effective sentences. In addition, researchers are also interested because they want to show the truth of language in writing official letters, so that people do not view the letter only as a symbol or notification. The problem that is the object of research is as follows. Spelling in writing official letters, diction in writing official letters, effective sentences in writing official letters, and research applications on learning Indonesian in high school (SMA) at the Kiung Village Office. The method used in this research is descriptive method with a qualitative form of research, while the data in this study are written data about spelling errors, namely the use of spelling errors of official letters at the Kiung Village Office, Suti Semarang District, Bengkayang Regency. Analysis of Spelling Error Writing Letters found 15 errors in writing capital letters, Writing Letters and syllables 2 errors in writing capital letters, Writing Abbreviations and Abbreviations as many as 2 errors in writing capital letters, errors in punctuation errors in commas as many as 6 errors. Keywords: Diction, Effective Sentences, Kiung Village, Service Letter, Spelling